The Influence of Sports on the Mental and Social Development of Early Childhood - Ridwan Ridwan (Siber International Journal of Sport Education, 2024)
This study aims to examine the impact of sports on the mental and social development of early childhood children at TK Perintis Bekasi Utara. A mixed-methods approach was employed, combining both quantitative and qualitative research methods. Quantitative data was obtained through the use of the Childhood Developmental Checklist (CDC) and surveys filled out by parents and teachers to measure children's mental and social development. Qualitative data was collected through interviews with teachers, parents, and sports coaches, as well as direct observations of children’s social interactions during sports activities. The results indicate that children who participated in the sports program showed significant improvements in mental development, including enhanced concentration, problem-solving skills, and emotional regulation. Socially, the sports group also showed significant improvement in communication, teamwork, conflict resolution, and emotional regulation. In contrast, the non-sports group showed only modest improvement in these areas. Statistical analysis showed that the sports group’s improvement in both mental (p < 0.05) and social (p < 0.05) development was statistically significant. These findings suggest that sports have a significant impact on both the mental and social development of early childhood children, and can serve as an effective tool to enhance social and emotional skills at this stage of development. Additionally, qualitative insights gathered from interviews and observations revealed that children who participated in sports exhibited better social interactions, improved empathy, and demonstrated stronger collaboration skills. Teachers and parents reported that these children were more confident in their social interactions and displayed greater emotional resilience in group settings. This study provides valuable insights for parents and educators to encourage children’s participation in sports as part of early childhood education programs. It is hoped that sports programs can become an integral part of supporting the holistic development of children.